An immune suppressive tumor microenvironment in primary prostate cancer promotes tumor immune escape. - Angelyn Anton; Ryan Hutchinson; Christopher M Hovens; Michael Christie; Andrew Ryan; Peter Gibbs; Anthony Costello; Justin Peters; Paul J Neeson; Niall M Corcoran; Ben Tran (PLoS ONE)
Background Immunotherapy has demonstrated limited activity in prostate cancer to date. This likely reflects an immune suppressive tumor microenvironment (TME), with previous studies suggesting low PD-L1 expression and a sparse immune cell infiltrate. We aimed to further characterise the immune TME in primary prostate cancer and correlate immune subset densities with clinical outcomes. Methods Two distinct cohorts of patients treated with radical prostatectomy were identified, based on the development of biochemical recurrence (BCR), one subgroup with high International Society of Urological Pathologists (ISUP) grade group, recurrent disease and a second with low grade, non-recurrent disease. A prostate immunohistochemical (IHC) antibody cocktail was used to differentiate tumor and peritumoral benign tissue. Specific CD8+, CD4+, FoxP3+, CD20+ and CD68+ cell subsets were identified using IHC staining of consecutive slides. PD-L1 and CD8/PD-L1 dual staining were also performed. Cell subset densities were quantified within tumor and peritumoral regions. We used descriptive statistics to report cell subset densities and T-tests to compare groups by age, grade and the development of BCR. Univariable and multivariable logistic regression were used to analyse risk factors for BCR and the development of metastatic disease. Results A total of 175 patients were included, with a median age of 63 years and median pre-operative PSA of 8.2ng/ml. BCR occurred in 115 patients (66%) and 56 (32%) developed metastatic disease. CD68+ cells were the most abundant (median 648.8/mm2 intratumoral, 247.6/mm2 peritumoral), while PD-L1+ and PD-L1/CD8+ cell density was low overall (PD-L1+ median 162.4/mm2 intratumoral, 141.7/mm2 peritumoral; PD-L1/CD8+ (median 5.52/mm2 intratumoral, 3.41/mm2 peritumoral). Overall, grade group and T-stage were independently associated with BCR and metastatic disease. Higher density of peritumoral PD-L1+ cells was an independent risk factor for BCR (OR 5.33, 95%CI 1.31-21.61, p = 0.019).Although higher densities of CD8+ and CD4+ cells were observed in higher grade group 3-5 tumors, these were not associated with the development of BCR or metastasis. Conclusions In our cohort of prostate cancer patients who underwent radical prostatectomy, higher grade group and T-stage were independent predictors of BCR and metastasis. Despite higher grade group being associated with higher CD8+ cell density, PD-L1+ and PD-L1/CD8+ cell densities were low overall, suggesting lower T cell receptor recognition of tumor antigens. Further understanding of this phenomenon would influence development of future immunotherapeutic strategies in prostate cancer.